Review on the book: Ashmanov I. S. and Kaspersky N. I. (2021) Digital Hygiene, Piter, St. Petersburg, Russia (In Russian) - G. V. Osipov (Цифровая социология)
As part of this work, a review of the book “Digital Hygiene” by Igor Stanislavovich Ashmanov and Natalia Ivanovna Kasperskaya was prepared. The review covers the content of the book, its main sections. The work provides a deep analysis of network threats and is valuable and timely. The book “Digital Hygiene” presents the mechanisms for protecting the individual in the virtual space, describes the general principles of digital hygiene, the use of which is of particular value to children and adolescents. Particular attention is paid to ways of early recognition of manipulations and network manipulators. The authors give their reasoned and balanced position on the prospects for the Internet and social networks development, dwell in detail on possible scenarios, including negative, the digital technologies development and their widespread introduction into society. The book “Digital Hygiene” in the context of the widespread penetration of innovations into our lives will be of interest to anyone who wants to protect themselves from the harmful effects of the uncontrolled spread of digital technologies. It will also be of interest to parents and school teachers. In addition, reading the book will be useful for ofﬁcials and civil servants who work in the ﬁeld of innovative development and digitalization. This publication is in demand and extremely relevant; on the basis of the book, a number of practical educational publications for teachers and parents should be prepared.